60%, -4% and 6%, a tale of thresholds for EU fiscal and current account developments - Afonso, António (2021)
We study the relationship between the budget balance and the current account balance for European Union (EU) countries, using quarterly data from 1995 to 2020. Through the use of panel Granger causality tests and a panel SUR model, we conclude that the relationship is bi-directional for the EU panel as a whole. Furthermore, we find that in Eurozone countries, before 2010, for those countries with an average current account balance-to- GDP ratio outside the range of -4 to 6%, and also in countries whose average debt-to- GDP ratio is greater than 60%, the impact of the budget balance on the current account balance is greater. Conversely, in non-Eurozone countries, after 2010, in countries with a current account balance-to-GDP ratio of -4 to 6%, and also in countries with an average debt-to-GDP ratio of less than 60%, the impact of the fiscal balance on the current account balance is less relevant.